PERSEPSI MAHASISWA HUBUNGAN INTERNASIONAL DI YOGYAKARTA MENGENAI KESIAPAN INDONESIA MENJELANG ASEAN COMMUNITY 2015 - Istiqomah Nuzula (HI 15 UMY 021, 2015)
*21 Indonesia with its young generations has to follow all aspects of ASEAN Community 2015 because Indonesia still has encumbrances to face the programs of ASEAN. The study is qualitative to know some aspects where the most knowledge aspect about ASEAN is in good category (164 students or 82%), the most conviction about the form ASEAN is in enough category (110 students or 55%) and the most value about source information of ASEAN is in enough category 136 students or 68%). Perception of International Relations students in Yogyakarta has value that Indonesia has not been ready to face ASEAN Community 2015